2017
DOI: 10.1136/thoraxjnl-2016-209265
|View full text |Cite
|
Sign up to set email alerts
|

Phage therapy is highly effective against chronic lung infections withPseudomonas aeruginosa

Abstract: With an increase in cases of multidrug-resistant Pseudomonas aeruginosa, alternative and adjunct treatments are needed, leading to renewed interest in bacteriophage therapy. There have been few clinically relevant studies of phage therapy against chronic lung infections. Using a novel murine model that uses a natural respiratory inhalation route of infection, we show that phage therapy is an effective treatment against chronic P. aeruginosa lung infections. We also show efficacy against P. aeruginosa in a biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(130 citation statements)
references
References 9 publications
1
126
0
3
Order By: Relevance
“…The overarching goal of each approach, however, focuses on how best to slow the emergence of resistance and control breakdown. Bacteriophages have been employed successfully in certain instances to treat animal 53–55 and plant 56 infections, and are thought to be particularly advantageous over traditional antibiotics because of their ability to amplify in the presence of their target host 57 and to overcome resistance through reciprocal coevolution. However, concerns remain, regarding the ability of phages ability to both promote horizontal gene transfer of potentially pathogenic determinants and to shift host tropism 58 .…”
Section: Discussionmentioning
confidence: 99%
“…The overarching goal of each approach, however, focuses on how best to slow the emergence of resistance and control breakdown. Bacteriophages have been employed successfully in certain instances to treat animal 53–55 and plant 56 infections, and are thought to be particularly advantageous over traditional antibiotics because of their ability to amplify in the presence of their target host 57 and to overcome resistance through reciprocal coevolution. However, concerns remain, regarding the ability of phages ability to both promote horizontal gene transfer of potentially pathogenic determinants and to shift host tropism 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Twelve hours after the administration of bacteriophages, bacterial cells in the mouse sputum were counted; in all cases, these counts were shown to be statistically lower than that in the control group (i.e. bacterial cells were not detected when bacteriophages were administered 24 and 36 h after inoculation; Waters et al ).…”
Section: Nonclinical Studiesmentioning
confidence: 98%
“…A recent research letter by Waters et al highlighted the potential of inhaled phages by demonstrating the effects of their administration on a murine model of chronic lung infection with an epidemic strain of P. aeruginosa. 106 They report a significant reduction in bacterial Colony Forming Units (CFU) from lung homogenate when phage was administered intranasally at a variety of time points ranging from 24 to 156 h post-infection. Several studies have reported the in vitro activity of phages against P. aeruginosa in biofilms isolated from the sputum of infected CF patients, where multidrug-resistant P. aeruginosa represents an increasing clinical problem.…”
Section: Phage Therapymentioning
confidence: 99%